Diagnosis of endometrial hyperplasia in routine gynecological practice - Poliakova, Ye. M.; Lutsenko, N. S.; Haidai, N. V. (Zaporozhye Medical Journal, 2019)
Objective. To estimate the accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) in diagnosis of endometrial hyperplasia using transvaginal ultrasonography (TVS) versus histopathological findings. Materials and methods. This is a retrospective study of 156 patients who underwent hysteroresectoscopy or diagnostic curettage. A comparative analysis of the preoperative diagnosis according to the TVS and postoperative diagnosis according to the histopathological conclusion was performed. All the patients were divided into 2 groups based on the TVS results before the procedure. Group 1 included 71 women with preoperative diagnosis of endometrial hyperplasia. Group 2 consisted of 85 women who underwent hysteroresectoscopy or diagnostic curettage for some other reasons. Using the statistical and mathematical methods, we determined the diagnostic value of TVS for diagnosis of both endometrial hyperplasia and pathology requiring subsequent invasive intervention into the uterine cavity. Results. According to histopathological findings, endometrial hyperplasia was found only in 35 (49.30 % PPV) out of the 71 patients who were positively diagnosed using TVS. The other 36 patients (50.70 %) had a negative histopathological diagnosis. The women of Group 2 were diagnosed correctly (absence of endometrial hyperplasia) in 52 cases (61.18 % NPV), but findings were positive in 33 (38.82 %) women according to histopathological examination. The sensitivity of TVS in the diagnosis of endometrial hyperplasia was 51.47 % (95 %CI 39.03–63.78) and the specificity was 59.09 % (95 %CI 48.09–69.46). However, the absence of indications for invasive intrauterine intervention was observed only in 4.22 % of women in Group 1 and in 2.35 % in Group 2. Conclusions. TVS has a low diagnostic value to identify an endometrial hyperplasia. TVS has a high diagnostic value for determination of intrauterine pathology which requires further hysteroresectoscopy or diagnostic curettage. Low diagnostic value of TVS in the diagnosis of endometrial hyperplasia necessitates an additional analysis considering the qualification of specialists performing ultrasound, the adequacy of the MOH Order No. 676 fulfillment, warranting reflection of parameters such as the endometrium structure, polypoid inclusions, sound conductivity, outer contour of the M-echo and uterine cavity surface as well as the endometrial-uterine ratio calculation in peri-and post-menopausal patients.